FACTORS AFFECTING THE AMOUNT OF MONEY CIRCULATING IN INDONESIA - Idah Yuniasih,; Teny Agustina,; Linggariama,; Arman Syah Putra,; Nurul Aisyah, (Journal of Innovation Research and Knowledge, 2022)
money in Indonesia and what factors affect these factors. The method used in this research is to use the literature study method using the basics of journals and books that are in accordance with related research, therefore reading is the most basic thing in this research in order to find the latest novels. The problem raised in this study is how to find what factors influence the circulation of money in a country, especially Indonesia. The factors that influence can be seen in this study. The purpose of this research is how to find out what affects the circulation of money in a country. With this, it can be ascertained what are the advantages and disadvantages of a country in issuing money so that it is not excessive or insufficient.